Anesthesia in anti‐N‐methyl‐D‐aspartate receptor encephalitis – is general anesthesia a requisite? A case report = Anestesia em encefalite antirreceptor de N‐metil‐ d ‐aspartato – a anestesia geral é um requisito? Relato de caso - Chaw, S.H.; Foo, L.L.; Chan, L.; Wong, K.K.; Abdullah, S.; Lim, B.K. (Elsevier, 2017)
Anti‐N‐methyl‐D‐aspartate receptor encephalitis is a recently described neurological disorder and an increasingly recognized cause of psychosis, movement disorders and autonomic dysfunction. We report 20‐year‐old Chinese female who presented with generalized tonic–clonic seizures, recent memory loss, visual hallucinations and abnormal behavior. Anti‐N‐methyl‐D‐aspartate receptor encephalitis was diagnosed and a computed tomography scan of abdomen reviewed a left adnexal tumor. We describe the first such case report of a patient with anti‐N‐methyl‐D‐aspartate receptor encephalitis who was given a bilateral transversus abdominis plane block as the sole anesthetic for removal of ovarian tumor. We also discuss the anesthetic issues associated with anti‐N‐methyl‐D‐aspartate receptor encephalitis. As discovery of tumor and its removal is the focus of initial treatment in this group of patients, anesthetists will encounter more such cases in the near future.